The Role Of Islamic Religious Education Teachers In Improving The Spiritual Intelligence Of Students In Elementary School (Case Study at SDN 003 North Bontang, East Kalimantan) - Rusliana; Andi Fitriani Djollong; Sumadin; Amir Patintingan (EDUJAVARE: International Journal of Educational Research, 2026)
Education is directed not only toward cognitive strengthening but also toward the development of religious-spiritual strength, self-control, and noble character, positioning spiritual intelligence as a central aim of Islamic Religious Education (IRE) in elementary schools. This study aims to describe the condition of students’ spiritual intelligence, to analyze the role of IRE teachers in enhancing that intelligence, and to identify the supporting and inhibiting factors of that role at SDN 003 North Bontang. A qualitative case study design was employed. Data were collected through in-depth interviews with the principal, the vice-principal for curriculum, IRE teachers, classroom teachers, and students, complemented by participatory observation and documentation study. Data validity was established through source, technique, and time triangulation, while data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that students’ spiritual intelligence is evident in their awareness of worship, honesty, patience, empathy toward others, and the ability to derive meaning from life events, although development remains uneven across students. IRE teachers function as educators, role models, motivators, guides, and evaluators through meaningful instruction, exemplary worship practice, reinforcement of intrinsic motivation, personal guidance, and consistent religious habituation. Supporting factors include religious habituation programs, curricular support, and school-wide collaboration, whereas inhibiting factors include differences in family background, limited instructional time, and the influence of gadgets and out-of-school peer environments. The study confirms that students’ spiritual intelligence develops through a triadic pattern of meaningful learning, teacher exemplarity, and sustained school-culture habituation.